Incorporating human factors into the AMT selection : a framework and a process - Borges, Lilian Adriana (2010)
This thesis is concerned with the assessment of human factors relevant to the selection of AMT (Advanced Manufacturing Technologies). Human factors such as employee morale, labour flexibility and workers skills should be evaluated during the pre-installation planning, since they greatly influence the implementation outcome. For newly industrialised countries, in particular, incorporating human factors into the selection seems paramount. These economies are in the critical early stages of AMT adoption. Selection practices are often incompatible with the complexity of these technologies. Moreover, low rates of secondary education, scarcity of technicians, and problems with workforce flexibility reinforce the importance of assessing human factors before the actual technology installation. Although some methods have been proposed to evaluate intangible aspects such as the human factors, the lack of a structured approach to identify and quantify these items still constitutes a major obstacle. Furthermore, this approach should be easy to use and establish a common measure for the comparison of options. It should involve key stakeholders and seek consensus on the decision. Aiming to address this gap, the research was undertaken in three phases: theory building, refinement and testing. A preliminary framework was devised from the review of literature, interviews with experts, and a pilot case study. A process was developed to operationalise the framework. The approach was applied using action research in nine case studies in Brazil: a pilot case study in the theory building phase, four cases for refinement, and four firms constituted the final testing. Three main categories of human factors were proposed: labour flexibility, individual capabilities, and employee relations. Grouping these items was crucial to create a definition for these factors and facilitate their identification.Taguchi's Loss Function was used as evaluation method for the human factors and available AMT. The strategies developed for identification and evaluation represented an important theoretical contribution. The in-company applications corresponded to the main practical contribution of the research. Very positive feedback was obtained on the appropriateness of the approach to address identification and quantification issues.